Effectiveness of hand - thinking playing LEGO on stress parent - child interaction of children with learning disabilities - sara saleki; Biuok Tajeri; Hasan Ahadi (مجله علوم روانشناختی, 2019)
Background: Research has shown the effectiveness of games on various variables such as social abilities, communication, and reducing isolation in children with learning disabilities. But the effectiveness of Lego's skill-thinking game on parent-child interaction tension remains neglected. Aims: Therefore, the present study aimed to investigate the effect of Hand-Thinking Playing LEGO on stress parent-child interaction in children with learning disabilities. Method: The research method was quasi-experimental with pretest-posttest design with control group. the statistical society included all 3rd grade elementary school children with a learning disorder in reading and writing in Tehran. 50 children were selected through available sampling. then, 30 children with high levels of stress parent-child interaction were selected randomly and replaced in two groups of 15 people (one experimental group and one control group). each of the children in the experimental group received 12 sessions of Hand-Thinking Playing LEGO (Story Starter) by Lego Educational Group (2014) with a phonological awareness, once a week for 60 minutes. The research instrument consisted of, Parental Stress Index (PSI) by Abidin (1990). Results: Data were analyzed by ANCOVA analysis. Findings showed that lego skill-intellectual play had a significant effect with 95% confidence Interval on the level of stress parent-child interaction in terms of parents (P<0/05, F= 39/65). Conclusions: The results of this study showed that using Lego game can improving the problem solving and social relationships lead to Reduce child problems and increased sense of parental competence. Therefore Hand-Thinking Playing Lego as a new learning system, improved the parental stress of children with learning disabilities.